Cost of a learner in pediatric ED - Nagesh Jadhav; Keith Grams; Richard Alweis (Greater Baltimore Medical Center, 2019)
Background: Experiential learning in a cornerstone of medical education, but impacts throughput, utilization of resources and patient outcomes. Objectives: Our study sought to determine the cost of a resident across various throughput, utilization, and patient outcome measures. Methods: This retrospective study was conducted in 2016 in the pediatric emergency department of an urban tertiary care hospital. . We compared various throughput, utilization and patient outcome measures between resident-covered and nonresident-covered patients. A subgroup analysis was performed based on complexity as determined by CPT codes. Results: 33,278 patient encounters occurred between 1 January 2016, and 31 December 2016. Of these, 8,434 (25.42%) were resident-covered patients. Across all encounters, throughput, utilization and patient experience measures were unfavorable for the resident covered group. In subgroup analysis based on complexity of patients, throughput measures were either unfavorable or there was a trend towards unfavorability across all complexities for the resident covered group. Overall utilization and patient outcome measures were unfavorable in low and moderate complexity patients for the resident covered group. In high complexity patients, most of the utilization and patient outcome measures were similar in both groups. Conclusion: Presence of a resident led to unfavorable increases in many throughput, utilization and outcome measures, a difference which disappeared in most cases with higher complexity patients. Therefore, the cost of a resident may actually decrease with increasing patient complexity.